2016
DOI: 10.4254/wjh.v8.i30.1279
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of minimal hepatic encephalopathy following liver transplantation in Egyptian cirrhotic patients

Abstract: AIMTo evaluate the reversibility of minimal hepatic encephalopathy (MHE) following liver transplantation (LT) in Egyptian cirrhotic patients.METHODSThis prospective study included twenty patients with biopsy-proven liver cirrhosis listed for LT and twenty age- and sex-matched healthy control subjects. All underwent neuro-psychiatric examination, laboratory investigations, radiological studies and psychometric tests including trail making test A (TMT A), TMT B, digit symbol test and serial dotting test. The psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The therapeutic efficacy of internal medicine treatment is not ideal, and recurrent refractory HE accompanied by liver failure is an indication for liver transplantation[93].…”
Section: He Treatmentmentioning
confidence: 99%
“…The therapeutic efficacy of internal medicine treatment is not ideal, and recurrent refractory HE accompanied by liver failure is an indication for liver transplantation[93].…”
Section: He Treatmentmentioning
confidence: 99%
“…As regard central nervous system affection, there were seventeen publications, most of them studied hepatic encephalopathy from early detection, diagnosis, management and prognosis (288)(289)(290)(291)(292)(293), one article studied minimal hepatic encephalopathy in children (294). Also, sudomotor changes, extrapyramidal manifestations and depression were studied (295)(296)(297).…”
Section: Liver Cirrhosis and Its Complicationsmentioning
confidence: 99%
“…In Egypt, Osman et al (2016) found that 10% of postliver transplant patients had encephalopathy [4]. In Egypt, Gad et al (2015) found that 12.6 percent of such individuals had a similar frequency [5].…”
Section: Introductionmentioning
confidence: 99%